Optimization of Project Based Learning (PJBL) Model to Improve Vocational High School Students' Skills - Mohammad Yusuf; Mohammad Fathoni; Muhadhi Muhadhi; Tuwoso Tuwoso (International Journal of Educational Evaluation and Policy Analysis, 2025)
Project-Based Learning (PjBL) model is an approach that focuses on the active involvement of students in the learning process through real projects. This study aims to optimize the implementation of the PjBL model in improving the skills of Vocational High School (SMK) students, both in terms of technical skills (hard skills) and non-technical skills (soft skills). The research method used is a qualitative approach with case studies in several vocational schools. Data were collected through observation, interviews with teachers and students, and analysis of learning documents. The results of the study indicate that optimal implementation of PjBL can improve students' understanding of concepts, problem-solving skills, and collaboration and communication skills. In addition, challenges in implementing PjBL include limited facilities, teacher readiness, and the need for industry support in project development. Therefore, synergy between schools, industry, and government is needed to increase the effectiveness of PjBL in equipping students with skills relevant to the world of work.